(untitled) (Pedagogy of Higher and Secondary Education, 2008)
The article is devoted to the essence of interactive learning, the notions “interactive learning”, “interactive methods”, “interactiveforms of learning” and “interactive technologies” are differentiated. The classification o f interactive technologies, which has been worked out by the author, is presented.